Animal Husbandry Practices of Livestock Keepers in Mizoram: a Case Study - Lalhmunmawia; Das, Samares Kumar (International Journal of Bio-resource and Stress Management, 2018)
There is a dearth of literature on animal husbandry practices of Mizoram where people have traditionally been rearing pig and chicken along with subsistence cropping. A case study was conducted in a village of Mizoram to study animal husbandry practices followed by the livestock keepers to help R&D professionals plan and implement livestock development programs. Case study was done following the principles and methods of Participatory Rural Appraisal (PRA). Study reveals that pig, cattle, chicken, goat and duck were reared in the village. Besides green fodder, cattle were fed wheat flour and wheat bran; pigs were fed home-made feed; chickens were fed broiler ration and rice grain. Cattle and pigs were bred through artificial insemination (AI). Pigs were housed in traditional wooden pigsty. Chicken were sheltered in traditional coop during night, and cattle were sheltered in cattle shed. Villagers were depended on veterinary dispensary for livestock health care. Vaccination and deworming was done regularly in cattle and pig. Milk was sold to Mizoram Multi Commodity Producers Cooperative Union (MULCO) or middlemen. Pigs were slaughtered and sold as pork in the village. Rarely, cattle and chicken were also slaughtered and sold in the village. Eggs were rarely available and sold. Dung was used in bio-gas, or stored and sold as manure in nearby places. There is a scope to improve animal husbandry practices provided remunerative marketing facilities are there.